CORRELATION OF BODY MASS INDEX WITH ANEMIA IN ADOLESCENT GIRLS AT SECONDARY SCHOOL PGRI 2 JAMBI CITY - Aghadiati, Faradina; Sari, Yesi Mustika; Liani Setyarsih; Putri Lubis, Izmi Arisa; Wulandari, Alifah (Ridwan Institute, 2025)
Background: Anemia remains a major public health problem affecting adolescents worldwide, particularly girls who are vulnerable due to rapid growth and menstrual blood loss. In Indonesia, the prevalence of anemia remains high (25–40%), driven by poor dietary habits, low adherence to iron supplementation, and overall nutritional status. While Body Mass Index (BMI)-for-age is a recognized determinant of anemia risk, local evidence, particularly from Jambi City, remains scarce. Methods: This cross-sectional study involved 30 female students aged 15–18 years. The data utilized were collected during a Community Service Program (PKM). BMI for age z-scores were calculated using the WHO 2007 Growth Reference. Hemoglobin levels were measured using a portable hemoglobinometer (HemoCue Hb 301). The relationship between BMI-for-age categories (underweight, normal, overweight) and anemia status was analyzed using the Chi-square test. Results: The overall anemia prevalence was 40%. Based on BMI for age, participants were categorized as underweight (n=8), normal (n=18), and overweight (n=4). Anemia prevalence varied significantly across categories: underweight (75.0%) showed the highest rate, followed by normal (33.3%), and overweight (25.0%). Statistical analysis revealed a significant association between BMI-for-age and anemia (p = 0.041). Conclusions: Anemia was present across all BMI categories, with the highest prevalence among underweight adolescents. These findings indicate that nutritional status strongly influences anemia risk and should be prioritized in adolescent health programs. Integrating school-based strategies such as routine growth and hemoglobin monitoring, iron–folic acid supplementation, and engaging nutrition education.